Challenges in Diabetes Management Barriers and Support Systems in North India - Eric Kwasi Elliason; Atul Khajuria; Stephen Monday; J. Samuel Kamanda; Gagandeep Singh (Emerging Trends in Metabolites, 2025)
Background: The prevalence of Diabetes mellitus is ever growing in India and management of the disease is hindered by socio-economic, healthcare, and psychosocial barriers. Insofar as economic and social barriers pose challenges ranging from limited access to medical care, social stigma, specialist support leading to improper glycemic control, which is a strong predictor for diabetes complications, morbidity and mortality. Moreover, developing an understanding of systemic challenges and available supports is vital for improving diabetes care and controlling the disease. Methods: A sample of 1500 purposely selected respondents having diabetes from urban and rural district in North India participated in a cross-sectional survey. Participants were asked to provide demographic information alongside the self-reported financial and healthcare barriers, psychosocial challenges, and other forms of support. The resulting data was analyzed through SPSS version 27 for statistical tests of independence, including chi-square tests and logistic regression. Results: The most common reporting challenge was stress and psychosocial burden (15.7%). This was followed by lack of access to diabetes specialists (15.3%), lack of social support (14.7%), cost of medication (14.3%), and difficulty in maintaining healthy nutrition (13.9%). No relationship between place of residence (urban vs. rural) and types of diabetes management challenges was found (χ² = 3.097, p = 0.797). This suggests that barriers exist in both environments. Some level of gender differences in challenges were identified but were not significant (χ² = 5.453, p = 0.941). Participants reported moderate adherence to prescribed medication (Mean = 2.95, SD = 1.433) and minimal attendance with health care providers (Mean = 2.48, SD = 1.099). Conclusion: The study points out the existences of challenges in diabetes management, where psychological issues and enforcement concerns take precedence. While evident, diabetes-related challenges cut across gender and residential areas, which calls for systemic solutions. Improving the healthcare system, lowering the cost of treatment, providing psychiatric assistance, and enhancing the provision of diabetes care at the community level could work towards better diabetes management.
Keywords: Diabetes care; Northern India; access to healthcare; adherence to self-care; economic barriers; psychosocial barriers; rural and urban areas; social support